Speech language group therapy in the context of written language for deaf subjects in Southern Brazil. (2nd October 2017) - Guarinello, Ana Cristina; Massi, Giselle; Berberian, Ana Paula; Tonocchi, Rita; Valentin, Silvana Mendonça Lopes
ABSTRACT: This article aims to investigate deaf peoplés reasons to participate in a therapeutic group and to analyze some of their reflections on the use of written Portuguese language produced inside this group within a sociocultural perspective. It was carried out at a School for the deaf located in Curitiba, Paraná State/Brazil in a partnership with researchers of a university located in Southern Brazil. Eight deaf subjects, aged 14–33, participated in the group therapies. Data were collected during a semester of group therapies, with 18 weekly meetings, two-hour long each. The findings revealed that group therapy for deaf teenagers and adults had a significant result in these participants' writing. This type of intervention can allow researchers to be tailored to meet deaf people's specific needs in the written language.